2022
DOI: 10.1093/mtomcs/mfac077
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding and oligomerization properties of FurC (PerR) from Anabaena sp. PCC7120: an additional layer of regulation?

Abstract: Metal and redox homeostasis in cyanobacteria is tightly controlled to preserve the photosynthetic machinery from mismetallation and minimize cell damage. This control is mainly taken by FUR (ferric uptake regulation) proteins. FurC works as the PerR (peroxide response) paralog in Anabaena sp. PCC7120. Despite its importance, this regulator remained poorly characterized. Although FurC lacks the typical CXXC motifs present in FUR proteins, it contains a tightly bound zinc per subunit. FurC:Zn stoichiometrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The composition of the extracellular milieu defines microbial interactions with the environment-modulating processes such as intercellular communication, toxin production, or biofilm formation, tailoring bacterial ability to cope with different stresses ( 28 , 48 , 49 ). Previous studies point to FurC as an essential stress regulator, playing a central function in the modulation of peroxide, as well as light and nitrogen responses in Anabaena ( 30 , 31 , 50 52 ). Furthermore, genome-wide identification of novel direct FurC targets unveiled the role of this protein in the regulation of central carbon metabolism ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the extracellular milieu defines microbial interactions with the environment-modulating processes such as intercellular communication, toxin production, or biofilm formation, tailoring bacterial ability to cope with different stresses ( 28 , 48 , 49 ). Previous studies point to FurC as an essential stress regulator, playing a central function in the modulation of peroxide, as well as light and nitrogen responses in Anabaena ( 30 , 31 , 50 52 ). Furthermore, genome-wide identification of novel direct FurC targets unveiled the role of this protein in the regulation of central carbon metabolism ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…This fact is very interesting since the MCO mechanism is a complex mechanism that depends on the oxidative stress found in the cell but also on the iron and manganese availability so that FurC could be regulating its target genes integrating these three different signals. In fact, this mechanism of regulation in response to oxidative stress of FurC might be even more intricated, since a new in vitro regulatory mechanism for FurC activity was recently reported, evidencing that apart from the MCO, FurC undergoes a reversible oxidation through interdimer disulfide bridges formation under mild oxidant conditions and iron deficiency that reversibly prevents the in vitro binding to the DNA [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCC 7120 cells allowing the derepression of antioxidant enzymes to face oxidative stress situations [ 4 ]. More recently, it was shown that in fact the irreversible inactivation of FurC/PerR by Fe 2+ in aerobic conditions goes along with the incorporation of an oxygen atom into its structure as its observed for other PerR orthologs [ 5 , 6 ]. This study also disclosed the FurC/PerR metal binding and oligomerization properties describing an additional layer of regulation of the protein based on cysteine-based reversible oxidation, increasing the complexity of its regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…All REPA experiments were performed under aerobic conditions and in the presence of a reducing agent, which can help catalyze hydroxyl radical formation in the presence of iron (Kim et al, 1985;Netto & Stadtman, 1996). Similar reaction conditions have been shown to induce metal-catalyzed histidine oxidation of PerR regulators (Sarasa-Buisan et al, 2022). To determine whether TtPerR is susceptible to histidine oxidation in vitro, we incubated TtPerR aerobically in the presence of a reducing agent, supplemented with either buffer or Fe 2+ , and then analyzed protein composition by MALDI-TOF mass spectrometry.…”
Section: Iron and Manganese Differentially Regulate Ttperrmentioning
confidence: 99%